ADEM after ChAdOx1 nCoV-19 vaccine: A case report. (June 2022) - Rinaldi, Virginia; Bellucci, Gianmarco; Romano, Andrea; Bozzao, Alessandro; Salvetti, Marco
Acute disseminated encephalomyelitis (ADEM) is an inflammatory demyelinating disease of the central nervous system (CNS), clinically defined by an acute polyfocal neurological syndrome usually with monophasic course. ADEM often occurs after infections, but 5%–10% of cases are preceded by vaccinations. Several cases of ADEM have been described after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, whereas no case has been reported after adenovirus-vectored or mRNA COVID-19 vaccine administration. Here we describe a case of ADEM presenting 2 weeks after receiving the first dose of ChAdOx1 nCoV-19 vaccine. Patient clinical/magnetic resonance imaging (MRI) status spontaneously improved and rapidly resolved with corticosteroids. A 4-month follow-up showed complete recovery and no relapses.